1997
DOI: 10.1002/food.19970410612
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, carcass characteristics, organs measurement and haematology of broiler chickens fed a high fibre diet supplemented with antibiotics or dried yeast

Abstract: Onifade: Broiler chickens fed a high fibre diet with antibiotics or dried yeast Growth performance, carcass characteristics, organs measurement and haematology of broiler chickens fed a high fibre diet supplemented with antibiotics or dried yeast A. A. OnifadeFour antibiotics, namely procaine penicillin, tylosin, streptomycin and neomycin-oxytetracycline each at 150 mp -kg-', and four levels of dried yeast, viz. 1.5, 3.0, 4.5 and 6.5 g * kg-were incorporated into a basal high fibre diet containing 250 g kg-' p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 16 publications
3
23
1
1
Order By: Relevance
“…This disagreed with the findings of Al-Bowait and AlSultan (2006) who reported that DP had no significant effect on glucose concentration of birds fed with diet containing DP; however, it agreed with the findings of Onifade (1997) who reported that glucose was accentuated high when fibrous diet was fed to broilers. It seems this effect of fibrous material contributed to increase in gluconeogenesis activity.…”
Section: Discussioncontrasting
confidence: 57%
“…This disagreed with the findings of Al-Bowait and AlSultan (2006) who reported that DP had no significant effect on glucose concentration of birds fed with diet containing DP; however, it agreed with the findings of Onifade (1997) who reported that glucose was accentuated high when fibrous diet was fed to broilers. It seems this effect of fibrous material contributed to increase in gluconeogenesis activity.…”
Section: Discussioncontrasting
confidence: 57%
“…However, the ostrich chicks fed the diet containing the Thepax probiotic reduced the concentration of total cholesterol and increased the concentration of albumin as reported in broiler chickens fed diets containing the same probiotic (S. cerevisiae) (Onifide, 1997;Paryad & Mahmoudi, 2008). Fat deposition is commonly accepted to be correlated with total cholesterol, LDL and VLDL blood concentration, which mainly depends on the triglycerides removed from the plasma (Hermier, 1997;Musa et al, 2006).…”
Section: Haematological Parametersmentioning
confidence: 70%
“…The different microscopic counts of protozoa in the ruminal fluid were obtained with the technique of Coleman and Hall (1978). Cellulose activity into the rumen was measured by loss of weight of cotton thread inoculated in sacco during 24 h in each period (Onifade, 1997).…”
Section: Methodsmentioning
confidence: 99%